The BRICS in International Development - Gu, Jing.; Shankland, Alex.; Chenoy, Anuradha; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This book offers a comprehensive comparative perspective on the increasingly significant development cooperation activities of the BRICS. Providing a powerful set of insights into the drivers for engagement within each country, it brings together leading experts from Brazil, Russia, India, China, South Africa and OECD countries. The authors review the empirical evidence for the BRICS' modes of development cooperation and their geographical reach, and explore the historical background and patterns of international development engagement of each country. They also present a cutting-edge analysis of the broader geopolitical shifts, distinctive ideologies and normative discourses that are influencing and informing their engagement in increasingly ambitious joint projects such as the New Development Bank. This collection is essential reading for anyone seeking to understand the rapidly changing landscape of international development.
Introduction. International Development, South-South Cooperation and the Rising Powers; Jing Gu, Richard Carey, Alex Shankland, Anuradha Chenoy -- Chapter 1. Brazil as a development partner under Lula and Rousseff: Shifts and continuities; Bianca Suyama, Laura Trajber Waisbich and Iara Costa Leite -- Chapter 2. Russia: A re-emerging donor; Marina Larionova, Mark Rakhmangulov and Marc P. Berenson -- Chapter 3. India: From technical cooperation to trade and investment; Anuradha Chenoy and Anuradha Joshi -- Chapter 4. China on the move: The 'New Silk Road' to international development cooperation?; Jing Gu, Yunnan Chen and Wang Haibin -- Chapter 5. South Africa: security and stability in development cooperation; Neuma Grobbelaar -- Chapter 6. Civil society, BRICS and international development cooperation: perspectives from India, South Africa and Brazil; Melissa Pomeroy, Alex Shankland, Adele Poskitt, Kaustuv Kanti Bandyopadhyay and Rajesh Tandon -- Chapter 7. Looking across BRICS: An emerging international development agenda?; Anuradha Chenoy, Marina Larionova, Richard Manning and Jennifer Constantine.
Keywords: Political economy; Economic development; Social change